2020
DOI: 10.3390/su12135317
|View full text |Cite
|
Sign up to set email alerts
|

Does Good ESG Lead to Better Financial Performances by Firms? Machine Learning and Logistic Regression Models of Public Enterprises in Europe

Abstract: The increasing awareness of climate change and human capital issues is shifting companies towards aspects other than traditional financial earnings. In particular, the changing behaviors towards sustainability issues of the global community and the availability of environmental, social and governance (ESG) indicators are attracting investors to socially responsible investment decisions. Furthermore, whereas the strategic importance of ESG metrics has been particularly studied for private enterprises, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 59 publications
5
49
1
2
Order By: Relevance
“…Sustainable Development Goals (SDGs) are designed to help companies meet several challenges: reputational risk management, responding to phenomena such as globalization and digitalization, proper communication with stakeholders, and meeting investor requirements for greater reporting transparency [34]. Climate change, human capital issues [6], and the increasingly visible associated risks cause more and more companies and regulators to become aware of the importance of environmental, social, and governance activities and disclosures [35]. Acting in the direction of these three dimensions, any company demonstrates what is called "corporate social responsibility".…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Sustainable Development Goals (SDGs) are designed to help companies meet several challenges: reputational risk management, responding to phenomena such as globalization and digitalization, proper communication with stakeholders, and meeting investor requirements for greater reporting transparency [34]. Climate change, human capital issues [6], and the increasingly visible associated risks cause more and more companies and regulators to become aware of the importance of environmental, social, and governance activities and disclosures [35]. Acting in the direction of these three dimensions, any company demonstrates what is called "corporate social responsibility".…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
“…The downward trend in the non-financial disclosure index for the majority of them is confirmed once again, but most companies have improved their disclosure metrics during the analyzed period. In terms of performance, most studies identify positive relationships between sustainability practices and financial indicators [6,[48][49][50][51] or between CSR and companies' financial performance [52][53][54][55][56]. In their analysis of a considerable number of listed British companies, Li et al [50] found a positive association between the level of environmental, social, and corporate governance disclosure and the value of the company, suggesting that improved transparency and accountability and increased stakeholder trust play a significant role in increasing the value of the company.…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between environmental reporting, environmental performance, and economic performance has been the subject of research by [50], whose study using structural modelling confirmed that better environmental performance leads to significantly better economic performance and also to providing more extensive quantified environmental information. The positive relationship between social responsibility and economic performance has been discussed, described [51][52][53][54], and also confirmed by research [55,56]. Emilsson and et al confirmed a positive relationship between social responsibility and economic added value in a sample of Swedish companies [57].…”
Section: Selection Of Esg Indicatorsmentioning
confidence: 65%